Nanoenhancer for improving naked DNA electrotransfection In vivo - Wang, Yifei; Wang, Chunxi; Sylvers, Justin; Segura, Tatiana; Yuan, Fan (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Electrotransfection (ET) is a non-viral approach widely used for delivery of naked nucleic acids. Its efficiency can be increased in vitro by treatment of cells with various small molecule enhancers. However, these enhancers often fail to improve ET in vivo, presumably due to rapid clearance in tissues after local injection, reducing their cellular uptake. To this end, we propose to develop a new type of ET enhancers, which we term nanoenhancer, that diffuse slowly in tissues and are poorly absorbed by blood and lymph microvessels. Methods: Two nanoenhancers were synthesized with alginate (Alg) and chitosan (Chi) with or without poly (ethylene imine) (PEI). They were used to treat cells in vitro or mouse muscle in the hind leg in vivo prior to ET of plasmid DNA coding reporter genes. At 24 hours post ET, the efficiency of ET was quantified, and compared with that in the untreated controls. Changes in lysosomal size and acidity post nanoenhancer treatment were measured with fluorescence microscopy techniques. Results and discussion: We observed that the pretreatment of cells with the nanoenhancers could enhance the ET efficiency and cell viability in both C2C12 and HCT116 cells in vitro, and the nanoenhancer pretreatment had similar effects on the ET efficiency in vivo. Mechanisms of the enhancement were related to transient inactivation of lysosomal functions triggered by the nanoenhancer treatment. The concept of nanoenhancer will lead to development of new enhancers that can be used to improve ET efficiency in vivo, highlighting its potential in clinical applications.